Crisis and Tourism in Rural Areas. Strategies, Actors and Projects in Patagones District, Argentina (Revista LIDER, 2019)
Tourism in rural areas is presented as a complementary activity to the traditional ones, capable of generating socio-economic, cultural and territorial benefits. In this work, the socioeconomic potential for tourism development of rural areas of the Patagones district was analyzed as an innovative and dynamic activity, based on semi-structured interviews with rural producers and unstructured interviews with representatives of related institutions. An exploratory-descriptive investigation was carried out based on a bibliographic review in order to identify the characteristics that tourism presents in rural areas. 25 semi-structured interviews were conducted, during 2014 and 2015, to rural producers of the Patagones district. In addition, unstructured interviews were conducted during the same period of time to those responsible for different institutions present in the district. The results showed that the rural crisis suffered by the Patagones district camps generated uncertainty about the incorporation of new activities such as tourism and the existence of projects that account for their interest in tourism, being some of the inconveniences for their its development, a lack of knowledge on the subject and lack of consolidated official support. The study reveals the need for associativism among the actors involved in the implementation of tourism in a space dedicated to traditional agricultural activities. The projects that arose after the rural crisis in the district, follow the guidelines of the modality of tourism in the rural space, incorporating various activities according to the characteristics that each space has.